2020
DOI: 10.3390/en13215736
|View full text |Cite
|
Sign up to set email alerts
|

Soot Particle Size Distribution, Regulated and Unregulated Emissions of a Diesel Engine Fueled with Palm Oil Biodiesel Blends

Abstract: In this study, five fuels including pure diesel (B0), pure palm oil biodiesel (B100), and their blends (B10, B20, and B30) were investigated in relation to soot particle distribution and regulated and unregulated emission characteristics in a common rail direct injection (CRDI) diesel engine. The results indicated that CO, hydrocarbon (HC), and particulate matter (PM) regulated emissions were effectively controlled to a very low level by combining the addition of palm oil biodiesel (POB) to diesel with optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…A number of papers have studied the characteristics of emissions, performance and combustion of high-ratio biodiesel fuel and pure diesel fuel. The performance and emissions characteristics of biodiesel engines are mainly determined by engine type and its settings, engine emissions control technologies, testing methodology and biodiesel resources [1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, there is a lack of studies investigating the impact of high-ratio biodiesel blends fuel and pure biodiesel (B100) on the performance and emissions of advanced vehicle technologies.…”
Section: Introductionmentioning
confidence: 99%
“…A number of papers have studied the characteristics of emissions, performance and combustion of high-ratio biodiesel fuel and pure diesel fuel. The performance and emissions characteristics of biodiesel engines are mainly determined by engine type and its settings, engine emissions control technologies, testing methodology and biodiesel resources [1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, there is a lack of studies investigating the impact of high-ratio biodiesel blends fuel and pure biodiesel (B100) on the performance and emissions of advanced vehicle technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have proved higher HC emission during the combustion of bio-esters [45]. This may be due to the higher biodiesel viscosity which indirectly affects the droplet size of atomized fuel [67]. A greater diameter of aerosol particles may hamper complete fuel combustion, which consequently leads to increased HC emissions [68].…”
Section: Unburned Hydrocarbons (Hc)mentioning
confidence: 99%
“…Results indicated that the regulated emissions of CO, HC, and PM were decreased, and the total VOC emissions of B20 were lower than those with the other test fuels. Jun Cong Ge et al [8] investigated the soot particle distribution and regulated and unregulated emissions in a CRDI diesel engine using diesel and palm oil biodiesel blends. It was found that all the PM particles were less than 100 nm in diameter observed by TEM (Transmission electron microscopy), and the average diameters of primary particles were distributed between 20 and 26 nm.…”
Section: Introductionmentioning
confidence: 99%